If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -1(7x + 3) + -1(5x + -3) = 7 + -1(2x + 1) Reorder the terms: -1(3 + 7x) + -1(5x + -3) = 7 + -1(2x + 1) (3 * -1 + 7x * -1) + -1(5x + -3) = 7 + -1(2x + 1) (-3 + -7x) + -1(5x + -3) = 7 + -1(2x + 1) Reorder the terms: -3 + -7x + -1(-3 + 5x) = 7 + -1(2x + 1) -3 + -7x + (-3 * -1 + 5x * -1) = 7 + -1(2x + 1) -3 + -7x + (3 + -5x) = 7 + -1(2x + 1) Reorder the terms: -3 + 3 + -7x + -5x = 7 + -1(2x + 1) Combine like terms: -3 + 3 = 0 0 + -7x + -5x = 7 + -1(2x + 1) -7x + -5x = 7 + -1(2x + 1) Combine like terms: -7x + -5x = -12x -12x = 7 + -1(2x + 1) Reorder the terms: -12x = 7 + -1(1 + 2x) -12x = 7 + (1 * -1 + 2x * -1) -12x = 7 + (-1 + -2x) Combine like terms: 7 + -1 = 6 -12x = 6 + -2x Solving -12x = 6 + -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. -12x + 2x = 6 + -2x + 2x Combine like terms: -12x + 2x = -10x -10x = 6 + -2x + 2x Combine like terms: -2x + 2x = 0 -10x = 6 + 0 -10x = 6 Divide each side by '-10'. x = -0.6 Simplifying x = -0.6
| 2Y=3X-Y | | 3(-2)-1=-2-5 | | 3x+41=65 | | 12(-2b-12)=-6(-3b+10) | | -2x+1=3x-9 | | -5x=-2x-6 | | 7500x=5900x+88000 | | (x+72)(x+48)=6912 | | -15-32n=4(-8n+4) | | 120-5a+7=8a-16a-35 | | 8y+1=9y-7 | | 4x+89=7x-74 | | 3x+2=3x-3 | | 4h^2=-62h-30 | | 2x/3=15 | | 2x/3-9=32 | | (7x^2-3x-16)+(8x^2+8x)= | | 240x+35=5y+135x | | 3x^3=81 | | 6y=z | | 3(3e+2f)+yf+2=0 | | Y=5/2x+1 | | 4x+3x+5= | | 24+b=40 | | 38-y=250 | | 18+4y=2(3-y) | | c=P+3b+a | | 5/(b+5)-2/b | | 23x^2-15=6x | | 4/x=8/17 | | 9+4y=(3-y) | | -3(x+5)=2x+5 |